CRIMINAL ASPECTS OF INFRINGEMENT OF TRADEMARK RIGHTS - Andrius, Nevera; Danguolė, Klimkevičiūtė (Anales Universitatis Apulensis Series Jurisprudentia, 2013)
Abstract. Article analyses criminal acts provided in the Article 204 of the Criminal Code of the Republic of Lithuania and problematic aspects of the implementation of the state criminal jurisdiction. The main attention is devoted to the questions of damage and criminal acts. Article also discusses the problems of Lithuanian legal regulation related to the application of principles of the nationality, universality and representation principle of the state criminal jurisdiction. Keywords: Intellectual property, Trademarks, Criminal Law, Criminal liability.